Administrative reform in China: issues and prospects - Burns John P.
China's experience of organizational reform is representative of the country's attempts to implement more general administrative reform. Forty years of organizational reform have produced only short-term successes. In the 1988 reforms, leaders proposed for the reforms have been undermined by political,economic, and institutional problems. These include conflicting elite priorities, cycles of economic centralization and decentralization, the interdependence of government agencies and economic enterprises, and the lack of incentives to economize. Consequently, the organizational reform management institutions are very weak. Successful implementation of organizational reform in the future depends to large extent
Keywords: Administrative Reforms -- China; Administrative Reorganisation -- China